2013
DOI: 10.1111/1755-5922.12033
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF‐κβ and Oxidative Pathways in Atherosclerosis: Cross‐Talk Between Dyslipidemia and Candesartan

Abstract: Summary Purpose The objective of this study is to assess the effect of the candesartan on the progression of atherosclerosis through the downregulation of NF‐κβ and interference with oxidative pathway. Methods Twenty‐four rabbits were assigned to three groups: control group fed normal diet; induced untreated group fed 1% cholesterol diet; and treated candesartan group also fed 1% cholesterol diet. Plasma lipid profiles were measured, and ELISA for plasma cytokines and chemokine was performed. Analyses of NF‐κβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…Torres et al () investigated the effects of candesartan treatment in hypercholesterolemic rabbits and found reduced expression of ICAM‐1 and consequent macrophage accumulation in the sclera and choroid. Hadi et al () have reported that candesartan reduces cytokine (TNF‐α, IL‐6, and IL‐1β) and chemokine levels (MCP‐1) as well as plasma lipid profile including total cholesterol, triglycerides, and LDL‐C, while also increasing plasma HDL‐C levels in treated rabbits. Additionally, candesartan significantly attenuated atherosclerosis lesions via interference with NF‐κB and oxidative pathways (Hadi et al, ).…”
Section: Ras Pharmacological Inhibitors In the Treatment Of Inflammatory Diseasesmentioning
confidence: 99%
“…Torres et al () investigated the effects of candesartan treatment in hypercholesterolemic rabbits and found reduced expression of ICAM‐1 and consequent macrophage accumulation in the sclera and choroid. Hadi et al () have reported that candesartan reduces cytokine (TNF‐α, IL‐6, and IL‐1β) and chemokine levels (MCP‐1) as well as plasma lipid profile including total cholesterol, triglycerides, and LDL‐C, while also increasing plasma HDL‐C levels in treated rabbits. Additionally, candesartan significantly attenuated atherosclerosis lesions via interference with NF‐κB and oxidative pathways (Hadi et al, ).…”
Section: Ras Pharmacological Inhibitors In the Treatment Of Inflammatory Diseasesmentioning
confidence: 99%
“…It is known that free radicals mediate various signaling pathways that are involved in vascular inflammation and lipid oxidation in atherogenesis (Yancey et al, 2003;Haas and Mooradian, 2011). Oxidative stress is defined as the disturbed balance between cellular levels of free radicals and antioxidant defenses (Hadi et al, 2013). Excessive free radicals attack all types of biomolecules including lipids molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, candesartan was observed to attenuate NF-κB p65 activity in the rat model of acute myocardial infarction. Furthermore, Hadi et al reported that candesartan significantly attenuates atherosclerotic lesions and significantly reduces NF-κB activity in rabbits (34). In addition, Ishrat et al demonstrated that candesartan reduces hemorrhage in rat embolic stroke through a reduction in NF-κB activity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Candesartan has also been observed to inhibit LPS-induced gene expression through the suppression of MCP-1 protein concentrations in human renal tubular epithelial cells (36). Hadi et al reported that candesartan retards the progression of atherosclerosis via reducing MCP-1, NF-κβ and oxidative pathways (34).…”
Section: Discussionmentioning
confidence: 99%